2021
DOI: 10.1097/txd.0000000000001119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subclinical Borderline Inflammation on Kidney Transplant Outcomes

Abstract: Background. Surveillance biopsies permit early detection of subclinical inflammation before clinical dysfunction, but the impact of detecting early subclinical phenotypes remains unclear. Methods. We conducted a single-center retrospective cohort study of 441 consecutive kidney transplant recipients between 2015 and 2018 with surveillance biopsies at 6 months post-transplant. We tested the hypothesis that early subclinical inflammation (subclinical bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Molecular pathology studies have found overlap between gene expression patterns in indication biopsies with acute rejection and injury and biopsies with chronic allograft injury. [35][36][37][38] Given the mixed reports of the benefits of treating subclinical acute rejection, 29,[39][40][41] the potential relationship between time-zero histology and subsequent subclinical rejection needs further evaluation in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular pathology studies have found overlap between gene expression patterns in indication biopsies with acute rejection and injury and biopsies with chronic allograft injury. [35][36][37][38] Given the mixed reports of the benefits of treating subclinical acute rejection, 29,[39][40][41] the potential relationship between time-zero histology and subsequent subclinical rejection needs further evaluation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Surveillance biopsies were performed at 6 months post-transplant, as reported previously. 29 Indication biopsies were performed to investigate allograft dysfunction at the discretion of the treating physician.…”
Section: Immunosuppression and Surveillancementioning
confidence: 99%
“… 16 Borderline change is also reported to be independently associated with poor long term graft outcomes. 17 18 Thus, flat pattern peak causes the increased risk of BPAR and/or borderline change and can be associated with poor long term graft outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher normalized evDNA yield, evDNA copy number, and dd-evDNA copy number correlated with inflammation in the kidney allograft (specific Banff scores > 0). Previous studies have shown that subclinical inflammation is a relatively common finding in surveillance allograft biopsies, identifying a high-risk group of kidney recipients for poor subsequent outcomes (Seifert et al, 2021). Other studies focusing on kidney injury observed larger uEV size in properly controlled diabetic patients compared with healthy controls (Freeman et al, 2018), whereas no changes in uEV size were observed when comparing different groups of patients with acute or chronic glomerular disease (Dimuccio et al, 2020).…”
Section: Discussionmentioning
confidence: 99%